A method for preparing graphene conductive slurry by recycling secondary battery negative electrode
Through simplified mechanical crushing and pickling treatment, combined with freeze-drying and ultrasonic dispersion technology, the complexity of graphite recycling of waste secondary batteries is solved, and efficient graphene recovery and preparation of high-purity conductive paste are achieved. It is suitable for Secondary batteries and thermally conductive materials.
Patent Information
- Application Number
- CN202310561112.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-05-18
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2043-05-18
AI Technical Summary
In the prior art, the negative graphite recycling technology of used secondary batteries is complex and imperfect, with problems of environmental pollution and single raw materials, making it difficult to achieve efficient graphene recycling.
By mechanically pulverizing and pyrolyzing the negative electrode sheet of the waste secondary battery, combining pickling and freeze-drying treatment, graphene conductive paste is further prepared by ultrasonic dispersion, simplifying the steps and improving the recycling efficiency.
It realizes efficient recycling of graphene, with a recovery rate of ≥40%, a powder purity of ≥99.8%, and simplifies the operation steps, which are suitable for the applications of conductive and thermally conductive materials of secondary batteries.
Smart Images

Figure CN116812922B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of recycling of waste batteries, and in particular to a method for preparing graphene conductive slurry by recycling negative electrodes of secondary batteries. Background Art
[0002] With the acceleration of modernization, the consumption of secondary batteries in the global electronic products, electric vehicles and other industries is increasing, and the electronic waste generated by waste secondary batteries is also increasing rapidly. Conventional landfill and incineration of waste secondary batteries will cause environmental and safety problems. At present, the recycling of secondary batteries is mainly focused on the recycling of positive active materials such as cobalt, iron, manganese and other transition metals and positive and negative current collectors copper and aluminum, but the recycling technology and industry for negative electrode graphite are still not perfect. The green recycling process of waste secondary batteries is crucial to environmental protection and resource recycling and reuse.
[0003] Graphene is a two-dimensional carbon material with a single-atom thickness formed by a periodic arrangement of carbon atoms (in a benzene ring structure). It is favored by the industry for its excellent electrical, thermal, mechanical and optical properties. At present, the mainstream preparation method of graphene is the improved Hummer method, but it has certain environmental pollution and raw material limitations, specifically including the following two aspects: (1) The improved Hummer method prepares oxidized-reduced graphene, such as the Chinese patent documents with publication numbers CN103708445A and CN110606481A, which all involve highly corrosive oxidants (such as potassium permanganate, sodium nitrate, sodium thiosulfate, concentrated sulfuric acid, concentrated nitric acid, potassium dichromate, etc.). The use of these strong oxidants is not environmentally friendly and the manufacturing process is difficult to control; (2) The raw materials used are relatively single, such as natural graphite or expanded graphite.
[0004] A Chinese patent document with publication number CN111384462A discloses a method for preparing graphene by recovering graphite from negative electrode active materials of waste secondary batteries, comprising the following steps: (1) disassembling, separating, cleaning and drying the waste secondary batteries to obtain a crude negative electrode carbon material; (2) extracting and washing the crude negative electrode carbon material with a low eutectic solvent, and obtaining a negative electrode carbon material extracted with a low eutectic solvent after magnetic stirring, ultrasonic vibration, filtering and drying; (3) using the negative electrode carbon material in step (2) as a raw material to prepare graphene by a Hummers redox method.
[0005] A Chinese patent document with publication number CN113131029A discloses a method for recycling graphite negative electrodes of secondary batteries to regenerate graphene, comprising the following steps: taking out the graphite negative electrode of the secondary battery and placing it in a solution for pre-expansion, separating the copper foil and the graphite dispersion solution after sufficient reaction; obtaining black graphite after the graphite dispersion solution is neutralized, solid-liquid separated, pickled and dried, and preparing graphene after the black graphite is subjected to strong acid intercalation, oxidant oxidation, hydrolysis, solid-liquid separation, pickled, dried and expanded.
[0006] However, the above method has the problems of complicated steps, difficult to obtain raw materials and high equipment requirements. Summary of the invention
[0007] The present invention provides a method for preparing graphene conductive slurry by utilizing recycled negative electrodes of secondary batteries. The method combines the failure characteristics of negative electrode active materials in the late cycle of waste secondary batteries (layer peeling, increased interlayer spacing, structural collapse, etc.) and a specific preparation process to enable graphene to be quickly peeled off from the recycled negative electrode material. The steps are simple, and high-value application of waste secondary batteries is achieved.
[0008] The specific technical solutions adopted are as follows:
[0009] A method for preparing graphene conductive slurry by recycling secondary battery negative electrode comprises the following steps:
[0010] (1) After the recycled secondary battery is discharged, the negative electrode sheet is disassembled and taken out, the negative electrode sheet is mechanically crushed and then thermally decomposed and peeled off, and solids with a particle size D50 less than 15 microns are collected after sieving as the negative electrode main powder;
[0011] (2) The negative electrode main powder is pickled, and the material temperature of the pickling system is maintained at 80-90° C. to obtain an upper acidified suspension; the acid used in the pickling includes hydrochloric acid, nitric acid and hydrofluoric acid;
[0012] (3) freeze-drying the acidified suspension obtained in step (2) to prepare graphene, and further ultrasonically disperse the suspension to obtain a graphene conductive slurry.
[0013] Preferably, the recycled secondary batteries are waste secondary batteries whose actual capacity drops to less than 80% of the rated capacity, including lithium-ion batteries, sodium-ion batteries, and the like.
[0014] The main failure of waste secondary batteries in the late cycle is the failure of negative electrode active materials, the destruction of solid electrolyte interface membrane (SEI membrane) or the loss of electrolyte. Negative electrode materials such as natural graphite, artificial graphite, mesophase carbon microspheres, soft carbon, hard carbon, etc. are intercalated and peeled off by electrolyte solvents (such as PC solvent co-embedded). The peeled negative electrode materials are the main source of multilayer or few-walled graphene. At the same time, the volume change caused by the insertion and extraction process of lithium in each charge and discharge cycle also easily causes the surface of the negative electrode material to pulverize and fall off. Therefore, the negative electrode material in the late cycle of waste secondary batteries is easier to peel off than in the initial state, which is theoretically conducive to the extraction of graphene; further, the present invention adopts a specific process to crush and pyrolyze the negative electrode sheet, further acidify and oxidize it, and then freeze-dry it, so that the graphene is further separated under rapid shrinkage and expansion; finally, a graphene conductive slurry is formed by ultrasonic dispersion, and the graphene conductive slurry can be used for secondary battery conductive materials, thermal conductive materials, etc.
[0015] Preferably, in step (1), the recycled secondary battery is discharged to below 2 V, and the reversible lithium is deintercalated from the negative electrode into the positive electrode material, while reducing the safety risk of subsequent processing.
[0016] Preferably, the negative electrode material in the recycled secondary battery includes at least one of natural graphite, artificial graphite, mesophase carbon microspheres, soft carbon, and hard carbon. The method of the present invention has good applicability, and the degree of difficulty of graphene exfoliation is, from easy to difficult: hard carbon>natural graphite>soft carbon>mesophase carbon microspheres>artificial graphite.
[0017] Preferably, the conditions for pyrolysis stripping are: air or nitrogen atmosphere, temperature 450-850°C, time 4-6 hours. If the temperature is too low, the binder (polymers such as SBR or PAA) and additives (CMC, etc.) in the negative electrode cannot be decomposed and the stripping effect cannot be achieved. If the temperature is too high, the energy consumption cost is increased and the high-temperature metal is easily oxidized, thereby introducing metallic copper impurities.
[0018] In step (2), the mass fraction of hydrochloric acid is 15% to 37%, the mass fraction of hydrofluoric acid is 20% to 50%, and the mass fraction of nitric acid is 30% to 90%; the dosage ratio of the negative electrode main powder, hydrochloric acid, hydrofluoric acid and nitric acid is 1:0.3:0.2 to 0.8:0.2 to 0.5. Specifically, the dosage of the three acids is adjusted according to the type and state of the negative electrode material.
[0019] Preferably, the pickling time is 12-36 hours.
[0020] Preferably, the freeze-drying step is specifically as follows: reducing the temperature of the acidified suspension to -40 to -85°C within 24 hours; and then drying at a vacuum degree of 13 to 26 Pa and a temperature of 25 to 45°C for 1 to 2 hours.
[0021] Ultrasonic dispersion can further disperse the agglomerated graphene obtained after freeze-drying to meet the requirements of processing and performance improvement. In step (3), the graphene is added to water or N-methylpyrrolidone and ultrasonically dispersed to obtain a graphene conductive slurry with a solid content of 0.5 to 55 wt %. Preferably, the power of ultrasonic dispersion is 500 to 1500 W, and the time is 0.5 to 2 h.
[0022] Preferably, in the graphene conductive slurry obtained by the method of the present invention, the number of graphene layers is ≤15 layers, and the specific surface area is 200-500m 2 / g, single-layer graphene thickness ≤20nm, flake size ≤15μm, powder resistance ≤25mΩ.cm; excellent performance.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The method of the present invention directly mechanically crushes the negative electrode sheets in the recycled secondary batteries and then pyrolyzes and peels them off, without the need to separate the negative electrode materials such as copper foil and negative electrode active materials. The steps are simple and easy to operate.
[0025] (2) The method of the present invention utilizes the characteristics of failure of negative electrode active materials in the late stage of waste secondary battery cycles (layer peeling, increased interlayer spacing, structural collapse, etc.), obtains recycled negative electrode materials through acid oxidation, and then freeze-dries in combination with the expansion and contraction characteristics of the material to quickly peel off the graphene, and finally prepares graphene conductive slurry through ultrasonic dispersion. The present invention utilizes the synergistic effect of waste secondary battery raw materials and specific processes to improve the efficiency of graphene recovery and realize the high-value application of waste secondary batteries; in the method of the present invention, the recovery rate of graphene is ≥40%, and the purity of the recovered graphene powder is ≥99.8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 This is an electron microscope image of the graphene obtained in Example 2.
[0027] Figure 2 This is an electron microscope image of the graphene obtained in Example 4.
[0028] Figure 3 Graphene Raman spectra obtained in Examples 1 to 6. DETAILED DESCRIPTION
[0029] The present invention is further illustrated below in conjunction with the examples and accompanying drawings. It should be understood that these examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The operating methods in the following examples without specifying specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturer.
[0030] The recycled secondary batteries in the embodiments are purchased from BYD, CATL, Guoxuan High-tech, China New Energy and other companies.
[0031] Example 1
[0032] (1) Discharge the recycled new sodium battery (positive electrode material includes layered oxide / negative electrode material includes hard carbon) whose actual capacity drops below 80% of the rated capacity to 0V, disassemble and remove the negative electrode sheet, mechanically crush the negative electrode sheet and then pyrolyze and peel it off. The pyrolysis and peeling conditions are: in air atmosphere, temperature 550°C, time 5.5h, collect the solid with particle size D50 <15 μm after passing through a 100-mesh sieve as the negative electrode main powder;
[0033] (2) The negative electrode powder is acid washed (acid ratio: 37% by mass HCl, 30% by mass HF and 80% by mass HNO 3 ; When the negative electrode main powder is 1kg, the amount of hydrochloric acid added is 0.3kg, the amount of HF added is 0.5kg, and the amount of HNO 3 The addition amount is 0.2kg; the material temperature is maintained at 80°C during pickling, the pickling time is 12h, and the upper acidified suspension is obtained;
[0034] (3) The acidified suspension was freeze-dried, the temperature of the upper acidified suspension was reduced to -45°C within 10 hours, and further dried at a vacuum degree of 20 Pa and a temperature of 35°C for 1.5 hours to prepare graphene, and the graphene was further added to N-methylpyrrolidone and ultrasonically dispersed at 500 W for 0.5 hours to obtain a graphene conductive slurry with a solid content of 3 wt%.
[0035] Example 2
[0036] (1) The recycled lithium-ion batteries (positive electrode materials include lithium iron phosphate / negative electrode materials include artificial graphite) whose actual capacity has dropped to less than 70% of the rated capacity are discharged to 1.5V, the negative electrode sheets are disassembled and taken out, and the negative electrode sheets are mechanically crushed and then pyrolyzed and peeled off. The pyrolysis and peeling conditions are: under nitrogen atmosphere, temperature 750°C, time 5h, and solids with a particle size D50 less than 15 μm are collected after passing through a 100-mesh sieve as the negative electrode main powder;
[0037] (2) The negative electrode powder is acid washed (acid ratio: 30% by mass HCl, 40% by mass HF and 68% by mass HNO 3 ; When the negative electrode main powder is 1kg, the amount of hydrochloric acid added is 0.3kg, the amount of HF added is 0.2kg, and the amount of HNO 3 The addition amount is 0.5kg), the material temperature is maintained at 85°C during pickling, the pickling time is 12h, and the upper acidified suspension is obtained;
[0038] (3) The acidified suspension was freeze-dried, the temperature of the upper acidified suspension was reduced to -85°C within 24 hours, and further dried at a vacuum degree of 10 Pa and a temperature of 45°C for 1.5 hours to prepare graphene, and the graphene was further added to N-methylpyrrolidone and ultrasonically dispersed at 1500 W for 2 hours to obtain a graphene conductive slurry with a solid content of 7 wt%.
[0039] Example 3
[0040] (1) Discharge the recycled NCM 811 ternary lithium battery (positive electrode material includes layered oxide NCM811 / negative electrode material includes natural graphite) whose actual capacity drops below 90% of the rated capacity to 1.5V, disassemble and remove the negative electrode sheet, mechanically crush the negative electrode sheet and then pyrolyze and peel it off. The pyrolysis and peeling conditions are: in air atmosphere, temperature 650°C, time 4h, and collect the solid with D50 <15 μm after passing through a 100-mesh sieve as the negative electrode main powder;
[0041] (2) The negative electrode powder is acid washed (acid ratio: 30% by mass HCl, 40% by mass HF and 68% by mass HNO 3 ; When the negative electrode main powder is 1kg, the amount of hydrochloric acid added is 0.3kg, the amount of HF added is 0.3kg, and the amount of HNO 3 The addition amount is 0.3kg), the material temperature is maintained at 80°C during pickling, the pickling time is 12h, and the upper acidified suspension is obtained;
[0042] (3) The acidified suspension was freeze-dried, the temperature of the upper acidified suspension was reduced to -55°C within 15 hours, and further dried at a vacuum degree of 25 Pa and a temperature of 35°C for 1.5 hours to prepare graphene, and the graphene was further added to water and ultrasonically dispersed at 800 W for 1 hour to obtain a graphene conductive slurry with a solid content of 5 wt%
[0043] Example 4
[0044] (1) discharging a lithium cobalt oxide battery (positive electrode material includes lithium cobalt oxide / negative electrode material includes mesophase carbon microspheres) whose actual capacity drops below 80% of the rated capacity to 1.7 V, disassembling and removing the negative electrode sheet, mechanically crushing the negative electrode sheet and then pyrolyzing and peeling it. The pyrolyzing and peeling conditions are: nitrogen atmosphere, temperature 700° C., time 6 h, and collecting the solid with D50 <15 μm after passing through a 100-mesh sieve as the negative electrode main powder;
[0045] (2) The negative electrode powder is acid washed (acid ratio: 30% by mass HCl, 40% by mass HF and 68% by mass HNO 3 ; When the negative electrode main powder is 1kg, the amount of hydrochloric acid added is 0.3kg, the amount of HF added is 0.3kg, and the amount of HNO 3The addition amount is 0.4kg), the material temperature is maintained at 80°C during pickling, the pickling time is 12h, and the upper acidified suspension is obtained;
[0046] (3) The acidified suspension was freeze-dried, the temperature of the upper acidified suspension was reduced to -75°C within 20 hours, and further dried at a vacuum degree of 25 Pa and a temperature of 35°C for 1.5 hours to prepare graphene, and the graphene was further added to N-methylpyrrolidone and ultrasonically dispersed at 800 W for 1 hour to obtain a graphene conductive slurry with a solid content of 5 wt%
[0047] Example 5
[0048] (1) A power-type lithium manganese oxide battery (positive electrode material includes spinel lithium manganese oxide / negative electrode material includes soft carbon) whose actual capacity drops below 80% of the rated capacity is discharged to 1.8 V, the negative electrode sheet is disassembled and taken out, the negative electrode sheet is mechanically crushed and then pyrolyzed and peeled off, and the pyrolysis and peeling conditions are: air atmosphere, temperature 650° C., time 5 h, and solids with D50 < 15 μm are collected after passing through a 100-mesh sieve as the negative electrode main powder;
[0049] (2) The negative electrode powder is acid washed (acid ratio: 30% by mass HCl, 40% by mass HF and 68% by mass HNO 3 ; When the negative electrode main powder is 1kg, the amount of hydrochloric acid added is 0.3kg, the amount of HF added is 0.25kg, and the amount of HNO 3 The addition amount is 0.5kg), the material temperature is maintained at 80°C during pickling, the pickling time is 12h, and the upper acidified suspension is obtained;
[0050] (3) The acidified suspension was freeze-dried, the temperature of the upper acidified suspension was reduced to -70°C within 15 hours, and further dried at a vacuum degree of 25 Pa and a temperature of 45°C for 1.5 hours to prepare graphene, and the graphene was further added to water and ultrasonically dispersed at 1000 W for 1 hour to obtain a graphene conductive slurry with a solid content of 5 wt%
[0051] Example 6
[0052] (1) discharging a power manganese iron phosphate battery (the positive electrode material includes olivine manganese iron phosphate lithium / the negative electrode material includes a composite material of natural graphite and artificial graphite) whose actual capacity drops below 80% of the rated capacity to 1.8V, disassembling and removing the negative electrode sheet, mechanically crushing the negative electrode sheet and then pyrolyzing and peeling it, the pyrolyzing and peeling conditions are: air atmosphere, temperature 650°C, time 4.5h, and collecting the solid with D50 <15 μm after passing through a 100-mesh sieve as the negative electrode main powder;
[0053] (2) The negative electrode powder is acid washed (acid ratio: 30% by mass HCl, 40% by mass HF and 68% by mass HNO 3 ; When the negative electrode main powder is 1kg, the amount of hydrochloric acid added is 0.3kg, the amount of HF added is 0.25kg, and the amount of HNO 3 The addition amount is 0.5kg), the material temperature is maintained at 80°C during pickling, the pickling time is 12h, and the upper acidified suspension is obtained;
[0054] (3) The acidified suspension was freeze-dried, the temperature of the upper acidified suspension was reduced to -65°C within 18 hours, and further dried at a vacuum degree of 25 Pa and a temperature of 45°C for 1.5 hours to prepare graphene, and the graphene was further added to water and ultrasonically dispersed at 1000 W for 1 hour to obtain a graphene conductive slurry with a solid content of 5 wt%
[0055] Sample analysis
[0056] Figure 1 This is an electron microscope image of the graphene obtained in Example 2, in which an obvious graphene sheet structure can be observed; Figure 2 This is an electron microscope image of the graphene obtained in Example 4, in which an obvious graphene sheet structure can be observed; Figure 3 1 is a Raman spectrum of graphene obtained in Example 1 to Example 6. In the six examples, the D peak and the G peak are relatively close, and there is no obvious 2D peak. It can be judged that Examples 1 to Example 6 can all obtain clear graphene oxide structures.
[0057] The physical properties of the graphene in the graphene conductive slurry obtained in Examples 1-6 were tested, and the results are shown in Table 1:
[0058] Table 1 Comparison of graphene properties in different examples
[0059]
[0060] The embodiments described above provide a detailed description of the technical solutions of the present invention. It should be understood that the above are only specific embodiments of the present invention and are not intended to limit the present invention. Any modifications, supplements or similar substitutions made within the scope of the principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing graphene conductive slurry by recycling secondary battery negative electrode, characterized in that: The following steps are involved: (1) After the recycled secondary battery is discharged, the negative electrode sheet is disassembled and taken out, the negative electrode sheet is mechanically crushed and then pyrolyzed and peeled off, and solids with a particle size D50 less than 15 microns are collected after screening as the negative electrode main powder; the pyrolysis and peeling conditions are: air or nitrogen atmosphere, temperature 450-850°C, time 4-6h; (2) The negative electrode main powder is pickled, and the material temperature of the pickling system is maintained at 80-90°C to obtain an upper acidified suspension; the acid used in the pickling includes hydrochloric acid, nitric acid and hydrofluoric acid; the mass fraction of hydrochloric acid is 15%-37%, the mass fraction of hydrofluoric acid is 20%-50%, and the mass fraction of nitric acid is 30%-90%; the dosage ratio of the negative electrode main powder, hydrochloric acid, hydrofluoric acid and nitric acid is 1:0.3:0.2-0.8:0.2-0.5; the pickling time is 12-36h; (3) freeze-drying the acidified suspension obtained in step (2) to prepare graphene, and further ultrasonically disperse the graphene conductive slurry; the freeze-drying step is specifically as follows: reducing the temperature of the acidified suspension to -40 to -85°C within 24 hours; and then drying it at a vacuum degree of 13 to 26 Pa and a temperature of 25 to 45°C for 1 to 2 hours.
2. The method for preparing graphene conductive slurry by recycling the negative electrode of a secondary battery according to claim 1, characterized in that: In step (1), the recovered secondary battery is discharged to below 2V.
3. The method for preparing graphene conductive slurry by recycling secondary battery negative electrode according to claim 1, characterized in that: The negative electrode material in the recycled secondary battery includes at least one of natural graphite, artificial graphite, mesophase carbon microspheres, soft carbon and hard carbon.
4. The method for preparing graphene conductive slurry by recycling secondary battery negative electrode according to claim 1, characterized in that: In step (3), graphene is added to water or N-methylpyrrolidone and ultrasonically dispersed to obtain a graphene conductive slurry with a solid content of 0.5 to 55 wt%.
5. The method for preparing graphene conductive slurry by recycling secondary battery negative electrode according to claim 4, characterized in that: The power of ultrasonic dispersion is 500-1500W, and the time is 0.5-2h.
Citation Information
Patent Citations
Method for preparing graphene powder material and graphene powder material
CN103708445A
Less-lamella graphene oxide dispersion liquid and preparation method thereof
CN110606481A
Method for preparing graphene by recovering graphite from waste lithium ion battery negative electrode material
CN111384462A
Method for recycling lithium ion battery graphite negative electrode to regenerate graphene
CN113131029A
Green recycling method of graphite negative electrode of waste lithium battery and graphene
CN114835109A
